1986
DOI: 10.1016/0022-4375(86)90067-8
|View full text |Cite
|
Sign up to set email alerts
|

The legal minimum drinking age in texas: Effects of an increase from 18 to 19

Abstract: Effects on motor vehicle crash involvement of raising the legal drinking age in Texas from 18 to 19 were examined, using an interrupted time-series design. Rates of single-vehicle-nighttime (SVN) and non-SVN crashes per 100,000 licensed drivers from 1978 through 1984 were examined for three levels of crash severity (serious injury, minor injury, property damage only) and four age groups (16-17, 18, 19-20, 21 and over). Resul's revealed significant reductions in SVN crashes for the 18-year-old target population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…Klepp et al (1996) found that implementation of the uniform minimum legal drinking age of 21 in the United States reduced the overall prevalence of drinking and driving, especially among those young people who had a few drinks. Other studies (e.g., Saffer & Grossman, 1987a, 1987bWagenaar, 1981Wagenaar, , 1986Wagenaar & Maybee, 1986) indicate that raising the minimum legal drinking age from 18 to 21 years decreased single vehicle nighttime crashes involving young drivers by 11% to 16% at all levels of crash severity. A 13% reduction in fatal nighttime crashes involving young drivers has also been reported in a study of 26 states when a higher drinking age law was enacted (DuMouchel et al, 1987).…”
Section: Retail Availabilitymentioning
confidence: 96%
“…Klepp et al (1996) found that implementation of the uniform minimum legal drinking age of 21 in the United States reduced the overall prevalence of drinking and driving, especially among those young people who had a few drinks. Other studies (e.g., Saffer & Grossman, 1987a, 1987bWagenaar, 1981Wagenaar, , 1986Wagenaar & Maybee, 1986) indicate that raising the minimum legal drinking age from 18 to 21 years decreased single vehicle nighttime crashes involving young drivers by 11% to 16% at all levels of crash severity. A 13% reduction in fatal nighttime crashes involving young drivers has also been reported in a study of 26 states when a higher drinking age law was enacted (DuMouchel et al, 1987).…”
Section: Retail Availabilitymentioning
confidence: 96%
“…These studies routinely have shovra that lowering the drinking age increases adolescent drinking and driving whereas raising the drinking age decreases adolescent drinking and driving (e.g. Cook & Tauchen, 1984;Smith, et al, 1984;Arnold, 1985;Wagenaar, 1986aWagenaar, , 1986bSaffer & Grossman, 1987). Similarly, studies show significant decreases in selfreponed drinking and purchases of alcoholic beverages by adolescents when the drinking age is raised (Williams & Lillis, 1986Coate & Grossman, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, by using automobile-related fatalities as outcome measures, this research has found that increased availability in the form of lower minimum drinking ages and lower prices was related to increased traffic fatalities (Wagenaar, 1986). For example, one such study (Wagenaar and Maybee, 1986) used time series techniques to demonstrate a decrease in all levels of traffic injury among 18-to 19-yearolds in the wake of an increase in the minimum drinking age in Texas. Additionally, increased physical alcohol availability has been linked to higher arrest rates for public drunkenness and drunk driving and to higher rates of cirrhosis mortality Watts, 1982, 1989;Rush et al, 1986).…”
mentioning
confidence: 96%